Association Between NPHS2 p.R229Q and Focal Segmental Glomerular Sclerosis/Steroid-Resistant Nephrotic Syndrome - Zhou, Qiongxiu; Weng, Qinjie; Zhang, Xiaoyan; Liu, Yunzi; Tong, Jun; Hao, Xu; Shi, Hao; Shen, Pingyan; Ren, Hong; Xie, Jingyuan; Chen, Nan (Frontiers in Medicine, 2022)
[Aim] NPHS2 is the coding gene of podocin. This study aims to investigate the association between NPHS2 p.R229Q (rs61747728), the most frequently reported missense variant of NPHS2, with focal segmental glomerular sclerosis (FSGS) or steroid-resistant nephrotic syndrome (SRNS) based on typing the variant in a Chinese FSGS/SRNS cohort and conducting a meta-analysis. [Method] We recruited patients with FSGS or SRNS, as well as healthy individuals. To conduct meta-analysis, all the studies on p.R229Q and FSGS/SRNS were searched from the public databases. [Results] Totally, we enrolled 204 FSGS patients, 61 SRNS patients [46 FSGS, 9 minimal change disease (MCD) and 6 IgA nephropathy (IgAN) patients] and 100 healthy controls. Unexpectedly, p.R229Q was absent in patients from our cohort. By meta-analysis of 21 studies including 2489 FSGS/SRNS patients and 6004 healthy controls, we confirmed the A allele of p.R229Q was significantly associated with an increased risk of FSGS/SRNS (allelic OR=1.90, 95%CI=1.44-2.52, P<0.001). However, subgroup analysis showed the association between p.R229Q and FSGS/SRNS was true only in Caucasians (allelic OR=2.14, 95%CI=1.54-2.98, P <0.001) and in early-onset patients (allelic OR: 2.13, 95%CI=1.21-3.76, P=0.009). [Conclusions] NPHS2 p.R229Q may play an important role in enhancing susceptibility of FSGS/SRNS, especially in ethnicity of Caucasians and in age of early-onset patients.